Kolaborasi Stakeholders Dalam Pengelolaan Taman Bungkul di Surabaya - Wati Nur Kumala, Gading Berlian; Raharjo, Atha Nabila; Musleh, Mohammad; Tamrin, M Husni (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
On 2013, Taman Bungkul Surabaya has become a city figure that is able to achieve international praise in the Best Parks in Asia group from the United Nations (UN), which includes a reminiscene of Sunan Bungkul. Bungkul Park collaboration in its management consists of the Trasportation Service, Cooperatives Service, UMKM, PDAM Surya Sembada, and the Environment Service. This research aims to analyze and describe the collaboration of green stakeholders located in the open space (RTH) of Bugkul Park, Surabaya. This research method includes qualitative descriptive research. The sources of data obtained came from observations of activities and events observed, and literature studies. In this research, it can be used as a benchmark for the success of collaboration in which there are eight variables, using theory according to (Edward DeSeve, 2007). The research results explain that the collaboration between stakeholders has been carried out well but is still not optimal overall. In the Taman Bungkul Surabaya green open space (RTH) collaboration, there are two indicators that support success, namely that there is no monopoly element and there are no controlling actors in a particular organization. However, there are also obstacles, including the lack of independence of information, lack of trust between stakeholders, and lack of commitment.